Itinéraires et prise en charge de jeunes filles en danger moral : l’exemple du centre polyvalent de Thiaroye au Sénégal - Mohamadou Sall (Sociétés et Jeunesses en Difficulté)
Senegalese families have been deeply affected by recent economic and social change, generating children’s marginality. The analysis of young girls’ biographies at Thiaroye Center shows that their marginality is generated by the bad quality of social ties resulting from several factors : plurality of absences, confusing references connected with their parents way of life, economic vulnerability (insufficient food) and daily experience of conflict, violence and maltreatment. The paper also shows that young girls can develop resilience when in care in a trustful environment.